2022
DOI: 10.3389/fimmu.2022.844931
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TNFR2 in Cancer: All Roads Lead to Rome

Abstract: TNF receptor 2 (TNFR2) has become one of the best potential immune checkpoints that might be targeted, mainly because of its vital role in tumor microenvironments (TMEs). Overexpression of TNFR2 in some tumor cells and essential function in immunosuppressive cells, especially regulatory T cells (Tregs), makes blocking TNFR2 an excellent strategy in cancer treatment; however, there is evidence showing that activating TNFR2 can also inhibit tumor progression in vivo. In this review, we will discuss drugs that bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…Tumor necrosis factor receptor 2 (TNFR2), the receptor of TNF, has been found that is highly expressed in humans and mouse Tregs, especially on eTregs. 81 , 82 , 83 , 84 , 85 Interestingly, the interaction of TNF with TNFR2 promotes suppressive function and phenotypical stability of Tregs. 86 , 87 Based on this interaction, Nie et al.…”
Section: Treg Subsets In Tumor Immunitymentioning
confidence: 99%
“…Tumor necrosis factor receptor 2 (TNFR2), the receptor of TNF, has been found that is highly expressed in humans and mouse Tregs, especially on eTregs. 81 , 82 , 83 , 84 , 85 Interestingly, the interaction of TNF with TNFR2 promotes suppressive function and phenotypical stability of Tregs. 86 , 87 Based on this interaction, Nie et al.…”
Section: Treg Subsets In Tumor Immunitymentioning
confidence: 99%
“…In vivo , TNFR2-overexpressing cancer cells promote the accumulation of TNFR2 + Tregs in the draining lymph nodes and increase the levels of sTNFR2 in the circulation ( 45 ). These studies suggest that elevated sTNFR2 could be an indicator of cancer ( 10 , 12 , 13 ). Therefore, the circulating sTNFR2 could potentially lend itself as a novel diagnostic biomarker to detect the presence of cancer.…”
Section: Introductionmentioning
confidence: 94%
“…TNFR2 is also highly expressed in immune cells, which could be associated with tumorigenesis and tumor growth or conversely tumor controls ( 10 , 12 , 13 ). This protein however has been shown to be broadly expressed in the repertoire of immunosuppressive cells present on tumors and tumor microenvironments promoting pro-tumor activity ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aggregated TNFR2 increases the density of receptor-associated intracellular proteins, triggering the activation of downstream canonical and noncanonical NF-κB pathways (1, 5,6). TNFR2 is primarily expressed in a subset of T cells, including regulatory T cells (Tregs) (7)(8)(9)(10), and TNFR2-mediated intracellular signaling expands Tregs, inducing cancer cell proliferation. Therefore, anti-TNFR2 antagonists are promising as a new type of immune checkpoint inhibitor to enhance the immune response in patients with cancer (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…TNFR2 is primarily expressed in a subset of T cells, including regulatory T cells (Tregs) (7)(8)(9)(10), and TNFR2-mediated intracellular signaling expands Tregs, inducing cancer cell proliferation. Therefore, anti-TNFR2 antagonists are promising as a new type of immune checkpoint inhibitor to enhance the immune response in patients with cancer (9)(10)(11)(12). In contrast, anti-TNFR2 signal-inducing antibodies (agonists) are pursued as therapeutic strategies to expand Tregs in autoimmunity, organ transplant rejection, and graft-versus-host disease.…”
Section: Introductionmentioning
confidence: 99%